2012
DOI: 10.4028/www.scientific.net/amm.246-247.1231
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nonspherical Particle Magnetorheological Greases with Computer Simulation Technology

Abstract: Based on computer simulation technology, we put forward the shear stress model of nonspherical magnetic particle MRG, and take the hexagon form magnetic particle MRG as an example; this paper deduces hexagon magnetic particle MRG shear stress formula. The model simulate and calculate the relationship between shear yield stress and magnetic field intensity respectively when radius and side length is equal and when the volume is equal also shear yield stress in the zero field condition. The simulation results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…However, the sedimentation problem still occurred in the plate-like particle-based MR fluids and the authors merely reduced the rate by up to 20% compared to the spherical particle-based MR fluids. Recently, Wei et al [ 14 ] studied the effects of using non-spherical particles in MR grease, where computer simulations were employed to observe the rheological properties. It was shown that the MR grease using hexagon-shaped magnetisable particles had higher magnetic field-dependent shear stress that increased from 7.4 to 21.7 kPa compared to the spherical particles (6.2 to 16.6 kPa).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sedimentation problem still occurred in the plate-like particle-based MR fluids and the authors merely reduced the rate by up to 20% compared to the spherical particle-based MR fluids. Recently, Wei et al [ 14 ] studied the effects of using non-spherical particles in MR grease, where computer simulations were employed to observe the rheological properties. It was shown that the MR grease using hexagon-shaped magnetisable particles had higher magnetic field-dependent shear stress that increased from 7.4 to 21.7 kPa compared to the spherical particles (6.2 to 16.6 kPa).…”
Section: Introductionmentioning
confidence: 99%
“…As surveyed from the above literature, studies on the comprehensive effects of the shape of particles on the magnetic field-dependent rheological performance of MR grease are considerably rare. To the best of the authors’ knowledge, studies into the effects of different particle shapes on the magnetic field-dependent performance of MR grease so far have been undertaken through simulation only [ 14 ], despite many works on the plate-like iron particle-based MR fluids via both simulation and experiment [ 10 13 , 16 , 18 ]. Consequently, the main technical contribution of this work was to experimentally investigate and compare the magnetic field-dependent rheological properties of MR grease with regard to two different particle shapes, namely plate-like CI particles and spherical CI particles.…”
Section: Introductionmentioning
confidence: 99%
“…The direction of the discrepancy between the input parameters and response parameter has been investigated through the multivariate regression equation based on ANOVA. Many rheological constitutive models for MR grease have showed the relation between yield stress and variables such as magnetic field strength and CIPs fraction in previous literature [11,24,41]. However, few investigations have queried the mechanism of the influence of CIPs fraction and SOV on field-dependent yield stress.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously, the synergistic effect of nanoadditives in the suspension did not reduce the yield stress at low magnetic field strength. To confirm whether different magnetic particle shapes affect the mechanical properties of the MR grease, Wei et al [24] calculated the shear yield stress based on computer simulation. It was found that MR grease with nonspherical (hexagonal) magnetic particles can produce larger shear yield stress compared to spherical particles.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to MR fluids, the rheological properties of MR greases such as the apparent viscosity, yield stress, shear stress, and storage or loss modulus can be controlled using an applied magnetic field . Apart from providing excellent dispersion stability for magnetic particles, greases present several advantages as carrier media, allowing for better determination and control of their initial viscosity and self‐sealing properties, compared to MR fluids . These characteristics have significant benefits, especially for applications in seismic controllable dampers and damping systems .…”
Section: Introductionmentioning
confidence: 99%